The Effectiveness of the PJBL Learning Model to Improve Students' Socialization Skills - nadia afista; fitri nanda shafira; risma iryani; garin ayu liwana (Journal of Pedagogical Content Knowledge, 2025)
The Effectiveness of the Project-Based Learning (PJBL) Learning Model to Improve Students' Socialization Ability. Problems that arise in the field show that the attitude of cooperation between students is still relatively low. They are more likely to prioritize their own egos, not want to accept suggestions from friends, dominate the group, and be passive when doing group assignments. This situation indicates a lack of social skills that needs to be corrected. Therefore, this research aims to explore the effectiveness of the Project-Based Learning (PJBL) learning model in improving students' social skills. PJBL is believed to be able to encourage cooperation, communication and collaboration among students because it focuses on projects that require active interaction and involvement of all group members. The method used in this research is a literature study, where data is collected from various relevant sources, including scientific articles and previous research. Based on the results of the literature review, it is hoped that the PJBL learning model can be an effective solution to overcome the problem of low social skills among students. With proper implementation, PJBL can help create a more inclusive learning environment and support the holistic development of students' social skills.